Vaccination versus antimicrobials to prevent Porcine Proliferative Enteropathy: associated costs and effects on piglets’ growth, health, and serological performance - Gallina, Marco Aurélio; Quirino, Monike Willemin; Frandoloso, Rafael; Tutida, Yuso Henrique; Norenberg, Adriano; Coldebella, Arlei; Bianchi, Ivan; Kich, Jalusa Deon (Frontiers in Veterinary Science, 2025)
IntroductionThis study evaluated vaccination and prophylactic use of antimicrobials as strategies to prevent Porcine Proliferative Enteropathy (PPE) during nursery and growth-finishing phases.MethodsThree hundred weaned piglets (~ 29 days old) were distributed into groups: NVMED – no vaccinated against Lawsonia intracellularis but in-feed medicated with antimicrobials (amoxicillin, florfenicol, lincomycin, spectinomycin and tilmicosin); VMED – vaccinated and in-feed medicated; VNMED – vaccinated but no in-feed medicated. Piglets were vaccinated at weaning (Porcilis® Ileitis, MSD Animal Health). The following variables were assessed: growth and health performance, anti-L. intracellularis IgG levels, L. intracellularis fecal shedding, Pneumonia and Pleurisy Index (PPI) at slaughter, antimicrobial consumption and costs, and vaccination expenses.ResultsAverage daily gain (ADG) at the nursery phase was lower in VNMED group (p < 0.01); however, there was no treatment effect on feed conversion, ADG, and body weight at growth-finishing phase (p ≥ 0.23). Similar anti-L. intracellularis IgG levels were found for VMED and VNMED groups at all evaluated moments (p = 0.01). L. intracellularis was only detected in feces samples from 4/90 tested piglets and no difference in health performance was found (p > 0.05). Groups presented PPI < 0.89. In-feed antimicrobial consumption and related costs were 3 to 3.5-fold higher for NVMED and VMED groups compared to VNMED group.DiscussionThe prophylactic administration of antimicrobials used in this study did not affect the serological performance post-vaccination against L. intracellularis. Additionally, vaccine use to prevent PPE reduced the antimicrobial consumption and related costs by ~70%, with no impairments on production outputs.